2021
DOI: 10.3390/jcm10112394
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Hearing and in Quality of Life after Sequential Bilateral Cochlear Implantation in a Consecutive Sample of Adult Patients with Severe-to-Profound Hearing Loss

Abstract: Bilateral cochlear implantation is increasing worldwide. In adults, bilateral cochlear implants (BICI) are often performed sequentially with a time delay between the first (CI1) and the second (CI2) implant. The benefits of BICI have been reported for well over a decade. This study aimed at investigating these benefits for a consecutive sample of adult patients. Improvements in speech-in-noise recognition after CI2 were followed up longitudinally for 12 months with the internationally comparable Finnish matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(57 reference statements)
1
7
0
Order By: Relevance
“…Although the number of bilateral CI users was small in this study, differences in speech production subdomain scores of bilateral CI users compared to those of bimodal and unilateral CI users showed both the reliability of the questionnaire and the positive effects of bilateral CI use on QoL. These data are consistent with the new reports [ 32 ]. Additionally, the highest scores in Tr-NCIQ were obtained in activity (in social domain) and basic sound perception (in physical domain), respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the number of bilateral CI users was small in this study, differences in speech production subdomain scores of bilateral CI users compared to those of bimodal and unilateral CI users showed both the reliability of the questionnaire and the positive effects of bilateral CI use on QoL. These data are consistent with the new reports [ 32 ]. Additionally, the highest scores in Tr-NCIQ were obtained in activity (in social domain) and basic sound perception (in physical domain), respectively.…”
Section: Discussionsupporting
confidence: 90%
“…The evaluation of the quality of life, employing the NCIQ pre- and post-CI has been examined in detail in previous studies [ 9 , 25 , 32 ], where a significant increase in post-implantation NCIQ scores has been reported. Since this study coincided with the COVID-19 pandemic, participants’ quality of life before and after implantation was not examined with the Tr-NCIQ and was not supported by objective audiological outcomes either.…”
Section: Discussionmentioning
confidence: 99%
“…Language development is directly proportional to intelligence and mental development. [6][7][8] Studies of factors that affect language development in children with CIs are limited in number in the literature. When the data of the current study were compared with the findings reported in the literature, it was seen that quite similar results were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…several studies have applied setups involving the presentation of speech from the front and noise from multiple spatially separated loudspeakers (17,(29)(30)(31)(32). In contrast, noise is typically only presented from one speaker from the front or from the side together with speech from the front for the evaluation of speech understanding in noise in standard audiological care (33)(34)(35)(36)(37)(38). Speech understanding in noise has been investigated in various studies in CI recipients using the directional microphones Standard, Zoom, and Beam with BTE sound processors.…”
Section: E92mentioning
confidence: 99%
“…Therefore, to assess speech understanding in spatially separated noise and the benefits of directional microphones in CI recipients with a larger ecological validity, several studies have applied setups involving the presentation of speech from the front and noise from multiple spatially separated loudspeakers (17,29–32). In contrast, noise is typically only presented from one speaker from the front or from the side together with speech from the front for the evaluation of speech understanding in noise in standard audiological care (33–38).…”
Section: Introductionmentioning
confidence: 99%